2010
DOI: 10.1007/s10620-010-1389-9
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Both Peroxisome Proliferator-Activated Receptor Delta and Cyclooxygenase-2 in Tissues Is Associated with Poor Prognosis in Colorectal Cancer Patients

Abstract: The expression of both PPAR δ and COX-2 in tissues may lead to liver metastasis and consequent poor prognosis in CRC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 28 publications
(30 reference statements)
0
36
0
1
Order By: Relevance
“…Moreover, we found a novel function of COX-2-derived PGE 2 signaling in mediating crosstalk between colonic tumor epithelial cells and macrophages. Our results indicate that both PPARδ and COX-2-derived PGE 2 signaling coordinately promotes colonic inflammation and colitis-associate tumorigenesis and is likely to be clinically relevant because the elevation of both PPARδ and COX-2 in tumor tissues correlates with a poor prognosis in CRC patients (43).…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, we found a novel function of COX-2-derived PGE 2 signaling in mediating crosstalk between colonic tumor epithelial cells and macrophages. Our results indicate that both PPARδ and COX-2-derived PGE 2 signaling coordinately promotes colonic inflammation and colitis-associate tumorigenesis and is likely to be clinically relevant because the elevation of both PPARδ and COX-2 in tumor tissues correlates with a poor prognosis in CRC patients (43).…”
Section: Discussionmentioning
confidence: 76%
“…Several studies have suggested that PPAR-δ expression has prognostic value for cancer patients including those with colorectal cancer (54, 55). However, there are inconsistencies in the reported PPAR-δ expression levels of different human tumors compared to normal tissue as well as how PPAR-δ expression correlates with prognosis.…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…First, PPAR / expression is elevated in colon cancer cells, and its endogenous activation has been proposed to mediate the pro-tumorigenic effect of PGs in the colon [370]. Importantly, tissue expression of PPAR / has been associated with poor prognosis in CRC patients [371], and its genetic disruption decreases the tumorigenicity of human colon cancer cells [372]. Moreover, repression of PPAR / by NSAIDs has been shown to mediate the tumor suppressor activity of these agents in CRC [373] and ovarian cancer [374] by a mechanism that includes a decrease of COX-dependent PG production and a direct inhibition of the DNA-binding activity of PPAR / .…”
Section: Ppar /mentioning
confidence: 99%